Effect of oral versus nasal breathing on muscular performance, muscle oxygenation, and post-exercise recovery - Lévénez, M.; Lévêque, C.; Lafère, C.; Guerrero, F.; Balestra, C.; Lafère, P. (Sports, 2025)
Nitric oxide (NO) plays a crucial role in muscle oxidative capacity, which predicts muscle strength. This study aimed to investigate whether different breathing techniques (nasal or oral breathing) affect muscle performance during acute exhaustive exercise. In our study, 49 healthy individuals (24 men /25 female; age 22.8 ± 3.4 years) performed two Wingate anaerobic tests in a counterbalanced order. Although perceived exertion was significantly higher with oral breathing (Borg Scale: 9.0 ± 1.1 vs. 8.0 ± 1.3, p = 0.04), breathing mode did not impact power output (peak: 749 ± 290 vs. 728 ± 284 W; average: 576 ± 217 vs. 575 ± 216 W, p = 0.2). NIRS data indicated no significant differences in muscle desaturation between the two breathing modes; however, nasal breathing resulted in significantly faster (0.45 ± 0.4 vs. 0.23 ± 0.12%/s, p = 0.02) and greater (75.2 ± 4.0 vs. 73.1 ± 3.6%, p = 0.04) post-exercise muscle recovery. As an indirect marker of NO bioavailability, flow-mediated dilation (FMD) was associated with a significant improvement (Pre: 107.4 ± 3.0% vs. Post: 110.3 ± 3.6%, p < 0.001) via nasal breathing only, with a significant difference between the two breathing modes (p < 0.0001). Therefore, we suggest that the nitrate-nitrite-NO pathway enhances muscle energy and function, which highlights the importance of nasal breathing.